INTERNALISASI DAN TRANSFORMASI NILAI-NILAI KEBUNGHATAAN MELALUI PEMBELAJARAN TEMATIK TERPADU DALAM MEMBENTUK KARAKTER PESERTA DIDIK SEKOLAH DASAR - Elliza Nofri Yenny; M. Nursi; Hendrizal; Ayumi Vesaka; Santi Eka Putri (STKIP Subang, 2026)
Character value internalization is an essential aspect of elementary education aimed at shaping students’ holistic personality. One relevant source of character values in the Indonesian educational context is the values of Kebunghataan, derived from Mohammad Hatta’s ideas, which emphasize honesty, responsibility, independence, democratic attitudes, and social justice. This study aims to describe the process of internalizing and transforming Kebunghataan values through integrated thematic learning in elementary schools. The research employed a qualitative descriptive approach. The research subjects included elementary school teachers and students, while data were collected through classroom observations, interviews, and document analysis. The findings indicate that Kebunghataan values can be effectively internalized through integrated thematic learning by embedding these values into learning objectives, instructional materials, learning activities, and teacher role modeling. Value transformation occurs when students not only understand the values conceptually but also demonstrate behaviors that reflect these values in learning activities and social interactions at school. This study concludes that integrated thematic learning has strong potential as a strategic approach to strengthening character education based on Kebunghataan values in elementary schools.